Expression Level of Heat Shock Protein in Blackgram under Elevated Heat Stress - Partheeban, C.; Jaivel, N.; Ragupathi, K. P.; Kavin, R. B.; Prithiviraj, K. (International Journal of Economic Plants, 2023)
The study was conducted at Department of Crop Management, Faculty center for Agricultural Education and Research, Ramakrishna Mission Vivekananda Educational and Research Institute, Coimbatore, Tamil Nadu, India (Latitude 11° 13’N, Longitude 76° 94’ E) from March, 2022 to June, 2022. Proteins play an indispensable role in bodybuilding. Thus, it is necessary to add the protein-rich food in daily diet. Black gram, one of the pulses, is being rich in proteins, which is about 20−25%. Heat is one of major important abiotic stress that affect the growth physiology and ultimately reduces the crop productivity. Heat stress majorly affects the reproductive phase and its leads decline in the yield. Plants can able to develop adaptive response to even mildest heat stress at morphological, physiological and biochemical levels. The main objective of this study was to evaluate the blackgram seedlings under high temperature to identify the expression level of heat shock protein for temperature stress tolerance. Heat tolerant plants develops the rapid phenological and biochemical changes which favors higher production. So, this study was carried out to evaluate the response pattern of blackgram under elevated temperature stress imposed on seedling stage in different genotypes. Six blackgram genotypes VBG-06-002, VBG-06-005, VBG-06-010, VBG-07-001, VBG-10-008 and COBG-759 were taken for this experiment. The protein profile as evidenced by SDS page analysis indicated distinct expression of 40 KDa protein in genotypes VBG-07-001, VBG-06-010, VBN-6 and COBG-11-02 not expressed in VBG-06-002 and COBG-759. This expression of protein maybe an indicative feature of thermo tolerance.